ClasSimVR - Park, Hayden; Cooper, Grant; Thong, Li Ping; Carr, Nicola (Valve Corporation, 2022)
The use of immersive virtual reality technology (IVR) has the potential to transform traditional educational practices. Within initial teacher education programs, IVR presents many opportunities as simulated classrooms can afford an accessible space for assisting pre-service teachers (PSTs) with learning and practicing the knowledge and skills required in the profession. The aim of this research is to demonstrate a proof-of-concept of IVR classroom that intends to assist pre-service teachers with learning school-wide positive behaviour interventions and supports (SWPBIS) strategies for supporting low-level challenging behaviours. This involves the design and development of an IVR classroom environment, ClasSimVR. To the best of our knowledge, this represents the first use of an IVR serious game for this purpose. This research contributes to the discourse surrounding the design, development, and implementation of both IVR environments and serious games for learning SWPBIS strategies within initial teacher education programs.